Odpowiedzi

Najlepsza Odpowiedź!
2010-03-21T09:54:53+01:00

kwadrat liczby oznaczam jako k
pierwiastek z liczby oznaczam jako p ;)

A= (3,4)
3k + 4k = xk
9 + 16 = xk
x = p25 = 5

B= (1,3)
1k + 3k = xk
1 + 9 = xk
x = p10

C= (-8,6)
(-8)k + 6k = xk
64 + 36 = xk
x = p100 = 10

D= (-3, -3)
(-3)k + (-3)k = xk
9 + 9 = xk
x= p18 = 3 pierwiastki z dwóch

E= (12, -5)
12k + (-5)k = xk
144 + 25 = xk
x= p169 = 13

:)


2 5 2
  • Użytkownik Zadane
2010-03-21T09:55:34+01:00
P- początek
wzór:
np.
|AB|²= (x₂ - x ₁)² + (y₂ - y₁)²

|AP|²= 3² + 4²= 9 + 16 = √25
|AP| = 5
|BP|² = 1² + 3² = 1+9= √10
|CP|²= (-8)² + 6²= 64 + 36 = √100
|CP|= 10
|DP|² = (-3)² + (-3)²= 9 + 9 = √18 = √9x 2= 3√2
|DP|= 3√2
|EP|²= 12²+ (-5)²= 144 + 25 = √169= 13
|EP| = 13
1 5 1